PROGRAM BRIEFS - Kelbessa, Addisu (Ethiopian Journal of Reproductive Health, 2018)
Engender Health is a leading global reproductive health organization that works in 27 countries e train local health professionals to provide high quality care to women and families to partner with governments and communities to make sure that every pregnancy is planned, every child is wanted, and every mother has the best chance of survival.